2017
DOI: 10.3389/fpls.2017.00632
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Flower Transcriptome between Grapevine Clones Are Related to Their Cluster Compactness, Fruitfulness, and Berry Size

Abstract: Grapevine cluster compactness has a clear impact on fruit quality and health status, as clusters with greater compactness are more susceptible to pests and diseases and ripen more asynchronously. Different parameters related to inflorescence and cluster architecture (length, width, branching, etc.), fruitfulness (number of berries, number of seeds) and berry size (length, width) contribute to the final level of compactness. From a collection of 501 clones of cultivar Garnacha Tinta, two compact and two loose c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 68 publications
2
30
0
Order By: Relevance
“…As a result, bunch compactness is becoming an important trait for clonal selection and grapevine breeding programs (Blaich et al, 2007;Regner, 2015), so a better understanding of this trait is needed. Tello et al, 2015) have recently identified three traits (rachis architecture, berry number and berry dimensions) as the main factors affecting bunch compactness variation in a multi-cultivar framework, whose developmental determination is controlled by diverse genetic and metabolic pathways (Deluc et al, 2007;Diaz-Riquelme et al, 2014;Grimplet et al, 2017;Li-Mallet et al, 2016). Differences in rachis architecture between loose and compact cultivars are mainly determined during the period of inflorescence development prior to anthesis (Shavrukov et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, bunch compactness is becoming an important trait for clonal selection and grapevine breeding programs (Blaich et al, 2007;Regner, 2015), so a better understanding of this trait is needed. Tello et al, 2015) have recently identified three traits (rachis architecture, berry number and berry dimensions) as the main factors affecting bunch compactness variation in a multi-cultivar framework, whose developmental determination is controlled by diverse genetic and metabolic pathways (Deluc et al, 2007;Diaz-Riquelme et al, 2014;Grimplet et al, 2017;Li-Mallet et al, 2016). Differences in rachis architecture between loose and compact cultivars are mainly determined during the period of inflorescence development prior to anthesis (Shavrukov et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The cluster I genes with down-regulation in loose clusters also encompass VIT_18s0001g04890 , annotated as a sulfate transporter. The two genes, VIT_18s0001g04890 and VIT_18s0001g03160 , have been described to be repressed in ‘Garnacha Tinta’ clones with larger berries (Grimplet et al 2017). This is in line with our results here for ‘Pinot Noir’ clones, as high MBV (mean berry volume) corresponds to large berries, which are an important determinant for loose clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Intravarietal diversity in cluster architecture sub-traits of grapevine cultivars has been reported in only a few cases, like ‘Garnacha Tinta’, ‘Tempranillo’, ‘Aglianico’ and ‘Muscat of Alexandria’ (Grimplet et al 2019; Grimplet et al 2017). For ‘Albariño’ clones and for ‘Pinot Noir’ clones the studies of Alonso-Villaverde et al (2008) and Konrad et al (2003) proved, that intravarietal cluster architecture variance correlates with the suseptebility to B.cinerea , i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors are effective on grape cluster compactness such as number and size of berries and length of peduncle and pedicels. The effective factors in grape cluster compactness have been investigated by microarray technology [46]. Transciptomic comparison for two clones related to Garnacha Tinta cultivar of grape, with different cluster compactness, indicated the high level of cell division in the earliest stages of flower development, plays an important role in the number and size of berries and, consequently, grape cluster compactness.…”
Section: Accepted Manuscriptmentioning
confidence: 99%